THE ROLE OF EASTERN SCIENTISTS IN INCREASINGDEVELOPING THE INTERESTS OF NATIONAL LEARNERS IN NATURE - Dilrabo Akhmedova (Galaxy International Interdisciplinary Research Journal, 2022)
This article is about the role of Eastern thinkers in increasing the interest of primary school students in nature, the development of social activity skills in students, spiritual and moral education, love of nature, good attitude to nature in our country to provide students with theoretical and practical knowledge.